Investigating pulmonary inflammation and injury after progressive systemic inflammation in preterm fetal sheep - Vandenberg, E. G.; Kelly, S. B.; Zahra, V. A.; Lu, H.; Thiel, A.; Hooper, S. B.; Galinsky, R.; Polglase, G. R. (Frontiers in Physiology, 2025)
IntroductionPreterm birth and intrauterine inflammation are commonly associated with lung inflammation and remodeling. We developed a fetal inflammatory response model using increasing doses of intravenous lipopolysaccharide (LPS) to cause systemic inflammation and injury. However, the effects of an increasing systemic inflammatory response on fetal lung inflammation and injury are not known. We aimed to investigate the effect of repeated increasing doses of intravenous LPS on pulmonary inflammation and injury in preterm fetal sheep.MethodsFetal sheep at 124 days of gestation (term ∼148 days) underwent surgical instrumentation. At 129 days of gestation, fetal sheep were randomized to saline control (n = 8) or repeated LPS infusions (300 ng/24 h then doubled every 24 h for 2 days; n = 8). Four days after LPS/saline infusions commenced, fetal lungs were collected for histological and molecular analysis of markers of pulmonary inflammation and injury.ResultsRepeated increasing doses of intravenous LPS decreased arterial pH, PaO2, SaO2 and increased lactate and PaCO2 compared to controls. LPS infusions caused a decrease in mRNA expression of pro-inflammatory cytokines IL1B (p = 0.030) and IL6 (p = 0.034) and an increase in IL18 (p < 0.0001). LPS exposure did not alter histological assessment of airway structure, elastin or collagen abundance, inflammatory cell infiltration or cell death compared to controls.ConclusionIntravenous administration of LPS did not cause fetal lung inflammation and injury assessed 4 days after LPS infusions commenced. Direct exposure to endotoxins within the lungs may be necessary to induce inflammation and injury in the fetal lungs.